Manganese doped-iron oxide nanoparticle clusters and their potential as agents for magnetic resonance imaging and hyperthermia. Issue 25 (10th June 2016) - Casula, Maria F.; Conca, Erika; Bakaimi, Ioanna; Sathya, Ayyappan; Materia, Maria Elena; Casu, Alberto; Falqui, Andrea; Sogne, Elisa; Pellegrino, Teresa; Kanaras, Antonios G.
Abstract : A method for water-soluble Mn doped iron oxide clusters and their magnetic properties. Abstract : A simple, one pot method to synthesize water-dispersible Mn doped iron oxide colloidal clusters constructed of nanoparticles arranged into secondary flower-like structures was developed. This method allows the successful incorporation and homogeneous distribution of Mn within the nanoparticle iron oxide clusters. The formed clusters retain the desired morphological and structural features observed for pure iron oxide clusters, but possess intrinsic magnetic properties that arise from Mn doping. They show distinct performance as imaging contrast agents and excellent characteristics as heating mediators in magnetic fluid hyperthermia. It is expected that the outcomes of this study will open up new avenues for the exploitation of doped magnetic nanoparticle assemblies in biomedicine.